Internal Medicine Residents’ Perceptions of Morning Report: a Multicenter Survey - Albert, Tyler J. (J Gen Intern Med, 2021)
BACKGROUND: Residents rate morning report (MR) as an essential educational activity. Little contemporary evidence exists to guide medical educators on the optimal content or most effective delivery strategies, particularly in the era of resident duty-hour limitations and shifts towards learner-centric pedagogy in graduate medical education. OBJECTIVE: Assess resident views about MR content and teaching strategies. DESIGN: Anonymous, online survey. PARTICIPANTS: Internal medicine residents from 10 VA-affiliated residency programs. MAIN MEASURES: The 20-item survey included questions on demographics; frequency and reason for attending; opinions on who should attend, who should teach, and how to prioritize the teaching; and respondents’ comfort level with participating in MR. The survey included a combination of Likert-style and multiple-choice questions with the option for multiple responses. KEY RESULTS: A total of 497 residents (46%) completed the survey, with a balanced sample of R1s (33%), R2s (35%), and R3s (31%). Self-reported MR attendance was high (31% always attend; 39% attend > 50% of the time), with clinical duties being the primary barrier to attendance (85%). Most respondents felt that medical students (89%), R1 (96%), and R2/R3s (96%) should attend MR; there was less consensus regarding including attendings (61%) or fellows (34%). Top-rated educational topics included demonstration of clinical reasoning (82%), evidence-based medicine (77%), and disease pathophysiology (53%). Respondents valued time spent on diagnostic work-up (94%), management (93%), and differential building (90%). Overall, 82% endorsed feeling comfortable speaking; fewer R1s reported comfort (76%) compared with R2s (87%) or R3s (83%, p = 0.018). Most (81%) endorsed that MR was an inclusive learning environment (81%), with no differences by level of training. CONCLUSIONS: MR remains a highly regarded, well-attended educational conference. Residents value high-quality cases that emphasize clinical reasoning, diagnosis, and management. A supportive, engaging learning environment with expert input and concise, evidence-based teaching is desired. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11606-020-06351-7.